Extending Agency Theory toward Conscious Agency in Sustainable Accounting and Reporting - Febrian Kwarto; Minanari; Fitri Indriawati; Zumratul Meini (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The increasing demands for sustainable accounting and sustainability reporting challenge the relevance of classical agency theory, which views agents primarily as rational and opportunistic economic actors. In practice, sustainability disclosure involves ethical, social, and environmental dimensions that transcend the traditional contractual relationship between principals and agents. This study aims to explore the limitations of classical agency theory in explaining sustainable accounting practices and to propose conceptual extensions that are more aligned with sustainability accountability. This study uses a critical conceptual literature review approach to previous studies on agency theory, corporate governance, and sustainability accounting. The results of the study show that classical agency theory still has limitations in explaining multi-stakeholder accountability, long-term orientation, and ethical considerations in sustainability reporting. As a conceptual contribution, this study proposes a conscious agency framework that positions agents as ethically and ecologically responsible actors and broadens the meaning of principals to include a wider range of stakeholders. This framework has implications for the development of sustainability accounting, governance mechanisms, and future empirical research agendas, particularly in the context of developing countries such as Indonesia.